Implikasi Komparatif Penerapan PSAK 239 dan PSAK 109 terhadap Penyajian Intrumen Keuangan Emiten BEI - Azhar, Muh.; Antong; Usman, Halim (Universitas Muhammadiyah Purwokerto, 2026)
This study aims to analyze the differences in financial instrument presentation when accounting standards are applied in different periods, namely the application of PSAK 71 (109) in 2017–2019 when PSAK 55 (239) was still effective, and the application of PSAK 55 (239) in 2020–2022 when PSAK 71 (109) was already in force. The method used is descriptive comparative with a simulation on the financial statements of PT Medco Energi Internasional Tbk for the 2017–2022 period. The results show that PSAK 71 produces higher allowance for impairment losses (CKPN), while trade receivables and other financial assets are lower compared to PSAK 55, due to the difference between the forward-looking Expected Credit Loss (ECL) and the reactive Incurred Loss Model (ILM). For derivative liabilities, no difference was found as both are measured at fair value through profit or loss. The implication highlights that the change in standards mainly affects the presentation of financial assets, while derivative liabilities remain relatively unaffected